2021
DOI: 10.3390/metabo11050260
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Agroclimatic Variables, Soil and Leaves Nutrient Status with the Yield and Main Composition of Kaffir Lime (Citrus hystrix DC) Leaves Essential Oil

Abstract: Previous studies revealed the impact growing location has on the quantity and quality of essential oils derived from numerous Citrus spp., except on the kaffir lime. This study aims to analyze the relationship shared by agroclimatic variables and soil-plant nutrient status to kaffir lime leaves essential oil yield and main composition. The experiment was conducted between February and April 2019 in four growing locations, namely Bogor (6°36′36″ S, 106°46′47″ E), West Bandung (6°48′12″ S, 107°39′16″ E), Pasurua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…However, a previous report on Citrus hystrix revealed that citronellol has a negative correlation with rainfall intensity [ 33 ]. Although a high variation was reported within individual flavonoid groups in response to elevational changes, it can be suggested that long days with cool night temperatures are the most crucial one for the biosynthesis of flavonoids [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a previous report on Citrus hystrix revealed that citronellol has a negative correlation with rainfall intensity [ 33 ]. Although a high variation was reported within individual flavonoid groups in response to elevational changes, it can be suggested that long days with cool night temperatures are the most crucial one for the biosynthesis of flavonoids [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…31 Perbedaan kandungan senyawa dalam minyak atsiri pada berbagai penelitian dapat dipengaruhi oleh metode ekstraksi yang digunakan. 31 Ragam kandungan senyawa dalam jeruk purut juga berhubungan dengan kondisi dimana jeruk purut ditanam, seperti kandungan sitronela akan tergantung pada pH tanah, sedangkan kandungan senyawa linalool berhubungan dengan ion K. 32 Efek insektisida pada nyamuk dewasa yang ditunjukkan dalam penelitian ini dapat menambah referensi mengenai pemanfaatan minyak atsiri jeruk purut dalam sediaan aromaterapi diffuser. Efek insektisida minyak atsiri jeruk purut terhadap serangga dengan berbagai bentuk sediaan juga telah banyak dilaporkan.…”
Section: Pembahasanunclassified
“…Leaf was an important variable to be an appropriate proxy of plant growth (Salazar et al 2018;Hamdani et al 2022), morphological feature (Efendi and Budiarto 2022;Budiarto et al 2021a;2021b;Djarot et al 2021), phytochemical content (Efendi et al 2021), and physiological condition (Budiarto et al 2018;Budiarto et al 2019b). Leaf size, in terms of leaf length and width, of sweet corn at present proved to be significantly affected by the application of PGR.In theory, the application of GA3 was able to increase leaf length by increasing plant cell division and elongation, but higher doses of gibberellic acid inhibited leaf growth yielding shorter leaves (De Souza and MacAdam 2001; Utami et al 2018).…”
Section: Leaf Length and Widthmentioning
confidence: 99%